2013
DOI: 10.1530/jme-13-0160
|View full text |Cite
|
Sign up to set email alerts
|

Different expression of TSH receptor and NIS genes in thyroid cancer: role of epigenetics

Abstract: The TSH receptor (TSHR) and sodium/iodide symporter (NIS) are key players in radioiodinebased treatment of differentiated thyroid cancers. While NIS (SLC5AS) expression is diminished/lost in most thyroid tumors, TSHR is usually preserved. To examine the mechanisms that regulate the expression of NIS and TSHR genes in thyroid tumor cells, we analyzed their expression after inhibition of ras-BRAF-MAPK and PI3K-Akt-mTOR pathways and the epigenetic control occurring at the gene promoter level in four human thyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 50 publications
1
43
0
Order By: Relevance
“…BRAF V600E is the most common genetic alteration found in PTCs [33] and is associated with a reduced expression of the genes involved in iodide metabolism [34], the presence of worrisome clinicopathologic features, and a significantly higher risk of recurrence than BRAF wild-type tumors [30,35]. In this series of PTCs, analysis of expression levels of thyroid-specific genes, which confirmed our previous finding regarding the presence of the lowest levels of NIS and the close to normal levels of TSH-R [21], revealed that THRβ expression was directly correlated with all the genes examined, suggesting for the loss of THR intra-thyroidal expression the behavior as a marker of differentiation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…BRAF V600E is the most common genetic alteration found in PTCs [33] and is associated with a reduced expression of the genes involved in iodide metabolism [34], the presence of worrisome clinicopathologic features, and a significantly higher risk of recurrence than BRAF wild-type tumors [30,35]. In this series of PTCs, analysis of expression levels of thyroid-specific genes, which confirmed our previous finding regarding the presence of the lowest levels of NIS and the close to normal levels of TSH-R [21], revealed that THRβ expression was directly correlated with all the genes examined, suggesting for the loss of THR intra-thyroidal expression the behavior as a marker of differentiation.…”
Section: Discussionsupporting
confidence: 88%
“…RNA concentration was measured by a NanoDrop Spectrophotometer (Thermo Fisher Scientific, Inc., Waltham, MA, USA). First-strand cDNA synthesis was performed following the protocol provided with the High Capacity cDNA Reverse Transcription kit (Life Technologies), as previously described [21].…”
Section: Rna Isolation From Thyroid Tissues and Reverse Transcriptionmentioning
confidence: 99%
“…Okada et al17 found that the expression of EpCAM in two anaplastic thyroid cancer cell lines (FRO and ACT‐1) were remarkably higher than those in the TPC‐1 and FTC‐133 cells. D‘Agostino et al clearly indicated that TSHR and NIS transcript levels in FTC‐133 cells are subjected to different forms of epigenetic control 19. We focused on detecting the methylation level of HORMAD2 and its impact on different subtype thyroid carcinoma (THCA) cells (TPC‐1 and FTC‐133) development.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, Pilli and coworkers (Pilli et al 2009) note that TSHR expression was not detected in any of a number of commonly studied cell lines. There are conflicting data regarding TSHR expression in the FTC-133 cell line (originating from a lymph node metastases of a differentiated human follicular thyroid cancer), with some authors demonstrating mRNA expression (D'Agostino et al 2014) and TSH ligand binding (Paolino et al 2014), which may represent heterogeneity within this cell line between laboratories. Additionally, there is conflicting evidence for TSHR expression in the BCPAP cell line (derived from a poorly differentiated PTC) (Pilli et al 2009, D'Agostino et al 2014, Dotan et al 2016.…”
Section: Tshr Expression In In Vitro Models Of Thyroid Cancermentioning
confidence: 99%
“…There are conflicting data regarding TSHR expression in the FTC-133 cell line (originating from a lymph node metastases of a differentiated human follicular thyroid cancer), with some authors demonstrating mRNA expression (D'Agostino et al 2014) and TSH ligand binding (Paolino et al 2014), which may represent heterogeneity within this cell line between laboratories. Additionally, there is conflicting evidence for TSHR expression in the BCPAP cell line (derived from a poorly differentiated PTC) (Pilli et al 2009, D'Agostino et al 2014, Dotan et al 2016. Similarly, PTC cells grown in thyrosphere culture lack expression of thyroid-specific proteins, and cells fail to produce cAMP in response to TSH stimulation , Giani et al 2015.…”
Section: Tshr Expression In In Vitro Models Of Thyroid Cancermentioning
confidence: 99%